La necesidad de garantizar el derecho a la naturaleza establecido en art. 72 de la constitución de la república del Ecuador, por medio de reformas al Cootad, a fin de crear un fondo de sostenibilidad para la restauración de bosques nativos - Quizhpe Tapia, Alex Patricio (2017)
The Ecuadorian State through the Political Constitution of 1998 guarantees in favor of people the Right to Nature, which is now part of the rights over renewable and non-renewable natural resources, as part of national sovereignty. At present, the charter or Constitution of Ecuador through the reform established in the constituent assembly of Montecristi in 2008, established that nature is subject of rights and that therefore any person or individual can manifest in its favor. Nature is currently subject to multiple effects that cause the loss of ecosystems and their biodiversity, which generates negative effects on the rights guaranteed by the State, such as living in a healthy environment, free and balanced, sustainable, without pollution; and equally affects the right of nature to be cared for, preserved and maintain its regenerative capacity. The rights of nature are guaranteed from the Constitution of the Republic of Ecuador, and the rights in favor of people to live in a healthy environment, are established in the international instruments that guarantee human rights to integral development. Our State, in its political constitution, guarantees in article 72 the right to the restoration of nature, and therefore of the native forests, that one of its main activities is reforestation, which is to guarantee compliance with The rights of nature, must be carried out in a technical and permanent way by the Decentralized Autonomous Governments. Through their legislative powers they must create fees, in order to obtain permanent resources, to reach the end of the restoration of degraded areas or areas, to guarantee the rights of nature.